2015
DOI: 10.3402/shv.v6.29183
|View full text |Cite
|
Sign up to set email alerts
|

Time strain among employed and self-employed women and men in Sweden

Abstract: Dual-earner families are common in Sweden, and most women are involved in the labour market. It has been shown that employees and self-employed individuals perceive their working conditions differently: self-employed individuals are more likely to experience an imbalance between work and family, higher job demands, and the feeling that they must be ''always on.'' Thus, there may also be a difference between employees and self-employed individuals in terms of perceived time strain. Previous studies have identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…4 , 5 Since self-employed persons are responsible for absolutely everything related to their own businesses, they become liable to exploitation at the workplace: they are more likely to work longer hours and to face difficulties in harmonizing their work and family life than waged employees. 5 , 8 , 23 The findings of the present investigation corroborate this outcome. Compared to employed workers, self-employed persons in both small businesses and in middle to large enterprises worked longer weekday hours and also worked more often on the weekends.…”
Section: Discussionsupporting
confidence: 89%
“…4 , 5 Since self-employed persons are responsible for absolutely everything related to their own businesses, they become liable to exploitation at the workplace: they are more likely to work longer hours and to face difficulties in harmonizing their work and family life than waged employees. 5 , 8 , 23 The findings of the present investigation corroborate this outcome. Compared to employed workers, self-employed persons in both small businesses and in middle to large enterprises worked longer weekday hours and also worked more often on the weekends.…”
Section: Discussionsupporting
confidence: 89%
“…A decade later, Fahlén (2014) presented evidence that women report higher levels of LIW than men do. Having greater responsibility for housework and family and child care and experiencing stress and time strain related to unpaid work seem to be risk factors for experiencing LIW (Byron 2005;Hagqvist et al 2015). These are tasks women have more responsibility for and spend more time on than men, which can be one reason why women report higher levels of LIW.…”
Section: Interference Of Work To Life and Life To Workmentioning
confidence: 99%
“…Generally, self-employed individuals are defined as workers who work independently from an employer and who pursue gainful activity on their own account, with or without employees. In comparison to employees, self-employed individuals seem to experience more conflicting demands between work and private life than regular employees (Nordenmark et al 2012;Bunk et al 2012) and greater time strains (Hagqvist et al 2015). However, there is a lack of consensus, as other research has found that employees report higher levels of conflict than self-employed individuals (Beutell 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Having a greater responsibility for housework, family and child care and experiencing stress and time strain related to unpaid work seem to be risk factors to experience LIW (Byron 2005;Hagqvist, Toivanen, and Vinberg 2015). These are tasks women have more responsible of, and spend more time on than men, which can be one reason explaining why women report higher levels of LIW.…”
Section: Interference Of Work To Life and Life To Workmentioning
confidence: 99%